Introduction to metadata - Baca, Murtha (2008)
Metadata, literally "data about data," provides a means of indexing, accessing, preserving, and discovering digital resources. The volume of digital information available over electronic networks has created a pressing need for standards that assist in locating, retrieving, and managing this vast and complex universe of information." "This revised edition of Introduction to Metadata, first published in 1998 and updated in an online version in 2000, provides an overview of metadata: its types, roles, and characteristics; a discussion of metadata as it relates to resources on the Web; a description of methods, tools, standards, and protocols that can be used to publish and disseminate digital collections; and a handy glossary." "Newly added to this edition are an essay on the importance of standards-based rights metadata to the activities of cultural institutions; a section entitled "Practical Principles for Metadata Creation and Maintenance"; and the latest information on metadata harvesting and the role of Google and other commercial search engines in the rapidly evolving field of digital libraries.